STUDI KASUS SISWA YANG MEMILIKI PERILAKU AGRESIF DI SD NEGERI SUNGAI RAYA - Aqila Syifa’aturrahmah; Yuline; Amallia Putri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to examine the characteristics, causal factors, and alternative support provided to sixth-grade students exhibiting aggressive behavior at Sungai Raya Public Elementary School. This study used a descriptive method with a qualitative approach in the form of a case study. Data collected through interviews, observations, and documentation were then analyzed using case study stages. The results showed that the first case subject tended to engage in verbal aggression, while the second case subject tended to engage in physical aggression. The contributing factors to the aggressive behavior of both students included internal and external factors. Alternative support provided included behavioral counseling with assertiveness training techniques, homework, and positive reinforcement for the first subject. The second subject was given response-building techniques, homework, and positive reinforcement. After five treatment sessions, both subjects showed positive changes.